Chapter Покоренная природа. Коренное население и эксплуатация земли в советской и постсоветской России в романах Прощание с Матерой Валентина Распутина и Зона затопления Романа Сенчина - CAPRIOGLIO, Nadia (Biblioteca di Studi Slavistici, 2018)
This essay analyses the individual's alienation from the natural environment caused by the commodification of nature. The analysis focuses on the novels "Proščanie s Matëroj" (Farewell to Matyora, 1976) by Valentin Rasputin and "Zona zatoplenija" (Flood Zone, 2015) by Roman Senčin, and seeks to highlight how literature, both in the Soviet Union and in modern Russia, deals with the critical discourse on environmental issues, the protection of nature, human freedom, and dignity of living beings.